Effects of exercise fatigue on plantar pressure in badminton : a exploratory study - Du, Y.; Wang, W. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of present study was to evaluate the effect of exercise fatigue on plantar pressure in badminton. One badminton athlete volunteer without any injury or disease in the latest 3 months attended this study. Peak pressure(PP) and integration of pressure and duration(Pt) of pelma pre- and post-fatigue were measured. Results show that PP of heel was the highest. After fatigue, the PP of heel and Pt of metatarsal were increased significantly, and the Pt of heel was decreased significantly. In badminton training, it's necessary to enhance muscular strength and arrange training intensity for individual. More and deeply biomechanical research should be done to lessen pain and injury.